Incidencia de los procesos de urbanización en el crecimiento económico de Ecuador a nivel provincial durante el periodo 2010-2020 - Tamayo Sarango, Diomedes Alexander (2022)
At the national level, economic growth has presented a cyclical behavior since ancient times, even reaching figures of -7.8% of GDP variation in 2020 as indicated by the World Bank [WB] (2022). Therefore, the main objective of this study is to evaluate the impact of urbanization on economic growth in Ecuador during the period 2010-2020, through an econometric study in order to propose policies based on urban concentration processes that stimulate economic growth. To this end, data were collected from the Central Bank of Ecuador [BCE] (2010-2022) and from various surveys conducted by the National Institute of Statistics and Census (INEC] (2010-2022), to subsequently apply Generalized Least Squares (GLS) models to estimate the relationship between urbanization and economic growth, and spatial models to detect the effect of nearby spaces and spatial spillovers. After applying the methodology, the main results indicate an inverted U-shape in Ecuador between urbanization and economic growth, and that spatially, urbanization negatively affects neighboring provinces. Finally, the application of a technology development program is recommended to create wealth spillovers, so that this knowledge from the more developed regions spreads to the less developed ones.